Oxygenation of the Intraportally Transplanted Pancreatic Islet - Thomas M. Suszynski; Efstathios S. Avgoustiniatos; Klearchos K. Papas (Journal of Diabetes Research)
Intraportal islet transplantation (IT) is not widely utilized as a treatment for type 1 diabetes. Oxygenation of the intraportally transplanted islet has not been studied extensively. We present a diffusion-reaction model that predicts the presence of an anoxic core and a larger partly functional core within intraportally transplanted islets. Four variables were studied: islet diameter, islet fractional viability, external oxygen partial pressure (P) (in surrounding portal blood), and presence or absence of a thrombus on the islet surface. Results indicate that an islet with average size and fractional viability exhibits an anoxic volume fraction (AVF) of 14% and a function loss of 72% at a low external P. Thrombus formation increased AVF to 30% and function loss to 92%, suggesting that the effect of thrombosis may be substantial. External P and islet diameter accounted for the greatest overall impact on AVF and loss of function. At our institutions, large human alloislets (>200 μm diameter) account for ~20% of total islet number but ~70% of total islet volume; since most of the total transplanted islet volume is accounted for by large islets, most of the intraportal islet cells are likely to be anoxic and not fully functional.